Contribution of the Alkylquinolone Quorum-Sensing System to the Interaction of Pseudomonas aeruginosa With Bronchial Epithelial Cells - Liu, Yi-Chia; Hussain, Farah; Negm, Ola; Paiva, Ana Carolina; Halliday, Nigel; Dubern, Jean-Frédéric; Singh, Sonali; Muntaka, Sirina; Wheldon, Lee; Luckett, Jeni; Tighe, Paddy; Bosquillon, Cynthia; et al. (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa causes infections in patients with compromised epithelial barrier function. Multiple virulence factors produced by P. aeruginosa are controlled by quorum sensing (QS) via 2-alkyl-4(1H)-quinolone (AQ) signal molecules. Here we investigated the impact of AQs on P. aeruginosa PAO1 infection of differentiated human bronchial epithelial cells (HBECs). The pqsA-E operon is responsible for the biosynthesis of AQs including the 2-alkyl-3-hydroxy-4-quinolones, 4-hydroxy-2-alkylquinolines and 4-hydroxy-2-alkylquinoline N-oxides as exemplified by PQS, HHQ and HQNO, respectively. PQS and HHQ both act as QS signal molecules while HQNO is a cytochrome inhibitor. PqsE contributes both to AQ biosynthesis and promotes virulence in a PQS-independent manner. Our results show that PQS, HHQ and HQNO were produced during PAO1 infection of HBECs, but no differences in growth or cytotoxicity were apparent when PAO1 and an AQ-negative ΔpqsA mutant were compared. Both strains promoted synthesis of inflammatory cytokines TNF-α, interleukin (IL)-6 and IL-17C by HBECs and provision of exogenous PQS negatively impacted on this response without affecting bacterial growth. Expression of pqsE and the PQS-independent PqsE-regulated genes mexG and lecA was detected during HBEC infection. Levels were reduced in the ΔpqsA mutant, i.e. in the absence of PQS, and increased by exogenous PQS. These results support a AQ-independent role for PqsE during initial infection of HBEC by P. aeruginosa and for PQS as an enhancer of PqsE and PqsE-controlled virulence determinants and as an immunomodulator.